Distribution of trace elements and total organic carbon in surface sediments of the Sulu and Sulawesi Seas (Taburan Unsur Surih dan Organik Karbon di permukaan sedimen di Laut Sulu dan Sulawesi) - Asamuddin, A.H; Mohamed, C.A.R (Universiti Kebangsaan Malaysia, 2011)
The concentrations of TOC, Al, Fe, Mn, Pb, Cu, Ni, Co and Cr in 27 surface sediments have been determined from the Sulu and Sulawesi Sesa during the ‘Saintifik Perdana 2009’ expedition cruise from 18 June to 1 August 2009. Sampling was conducted to elucidate concentrations and spatial distributions throughout the study area. The samples were digested using a total digestion technique and the concentrations were determined using the ICP-MS. The distribution of trace elements fluctuated with stations and water depth, but showed high metal concentrations in some locations such as Marudu Bay, Sandakan and Darvel Bay. The concentrations of trace elements were mostly lower than the earth’s mean crust and the world’s mean sediments with the exception of a few trace elements in certain stations. The Geoaccumulation Index (Igeo) was calculated and the results showed that Ni are in class 1 (unpolluted to moderately polluted) while other trace elements are considered unpolluted. It can therefore be concluded that the Sulu and Sulawesi Seas are unpolluted and pristine